An International Radiosurgery Research Foundation Multicenter Retrospective Study of Gamma Ventral Capsulotomy for Obsessive Compulsive Disorder. Issue 6 (22nd November 2018) - Gupta, Amitabh; Shepard, Matthew J; Xu, Zhiyuan; Maiti, Tanmoy; Martinez-Moreno, Nuria; Silverman, Joshua; Iorio-Morin, Christian; Martinez-Alvarez, Roberto; Barnett, Gene; Mathieu, David; Borghei-Razavi, Hamid; Kondziolka, Douglas; et al.
ABSTRACT: BACKGROUND: Obsessive compulsive disorder (OCD) across its full spectrum of severity is a psychiatric illness affecting ∼2% to 3% of the general population and results in significant functional impairment. There are few large patient series regarding Gamma ventral capsulotomy (GVC). OBJECTIVE: To evaluate clinical outcomes of severe medically refractory OCD treated with GVC. METHODS: This is an international, multicenter, retrospective cohort study. Forty patients with pre-GVC Yale-Brown Obsessive Compulsive Scale (Y-BOCS) scores ≥ 24 (indicating severe OCD) were included. GVC was performed with 1 or 2 isocenters with a median maximum dose of 135 Gy (range, 120-180 Gy). Patients were deemed "responders" to GVC if there was ≥35% reduction of follow-up Y-BOCS scores, and considered in remission if their Y-BOCS scores were ≤16. The median follow-up was 36 mo (range, 6-96 mo). RESULTS: The median pre-SRS Y-BOCS score was 35 (range, 24-40). Eighteen patients (45%) were considered "responders, " and 16 (40%) of them were in remission at their last follow-up. Nineteen patients (47.5%) remained stable with Y-BOCS of 33 (range, 26-36) following GVC, whereas 3 patients (7.5%) experienced worsening in Y-BOCS scores. Patients treated with 2 isocenters were more likely to have improvement in Y-BOCS score at 3 and 5 yr ( P  < .0005). Ten patients (25%) experienced post-GVC mood disturbance and neurological complications in 3 patients (7.5%). One patient developed radiation necrosis with edema that improved with steroids. CONCLUSION: GVC serves as a reasonable treatment strategy for severe medical refractory OCD. Patients treated with 2 isocenters were more likely to have substantial improvement in OCD.